The Best Open and Distance Learning (ODL) platforms for mathematics subjects based on student’s perspective using Fuzzy Analytical Hierarchy Process (FAHP) - Noraini, Ahmad (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2023)
Link to publisher's homepage at https://amci.unimap.edu.my/